Analysis Of The Effect Of Academic Support, Structural Support And Relational Support On The Entrepreneurship (Case Study Of Universities "X" Students In Semarang City) - Widaryanti, Widaryanti; Luhgiatno, Luhgiatno (Economics and Business Solutions Journal, 2018)
This study aims to analyze the effect of Academic Support, Structural Support and Relational Support on Entrepreneurial Intention. The population of this study was students of one of the Universities in Semarang City who had received entrepreneurship courses. The sample in this study obtained data as many as 140 respondents. This study uses a primary data collection method in the form of a questionnaire. The data analysis technique used is descriptive statistical analysis, classic assumption test, multiple linear regression analysis and hypothesis testing. Processing research data with the help of SPSS 18. The results of this study are Academic support influences the intention of entrepreneurship, structural support influences the intention of entrepreneurship and relational support influences the intention of entrepreneurship. Simultaneously the three variables of this study influence the intention of entrepreneurship.